A study on the infectious waste disposal practices of selected dentists in manila - Santos, Michelle
The research was performed to determine the infectious waste disposal practices of selected dentists in Manila. Questionnaires were administered to 100 dentists from various districts in Manila. From the 100 subjects, only 70 questionnaires were returned completed and considered valid for inclusion in the study. The information gathered were then processed and computed to determine the resultant mean and percentages of the various responses to the questions. Results of the study show that majority of the dentists are not practicing the recommended methods of waste disposal, specifically in their disposal of extracted teeth and pathologic tissues. 36 of the subject dentists disposed extracted teeth with the general waste, while 33 out of the 44 dentists who generate pathologic tissues disposed them together with the general waste. Primary reasons for disposing infectious waste with the general waste was the lack of available facilities. However, 44 out of 70 dentists claim to be aware of the existing DOH Guidelines concerning Infectious Waste Management. Thus, from the results gathered, it can be concluded from the study that the level of awareness of the dentists does not have a direct relationship with regards to their compliance to the recommended disposal practices.